1999
DOI: 10.1164/ajrccm.160.4.9808118
|View full text |Cite
|
Sign up to set email alerts
|

Bronchopulmonary Segmental Lavage with Surfaxin (KL4-Surfactant) for Acute Respiratory Distress Syndrome

Abstract: We performed a trial to assess the safety and tolerability of sequential bronchopulmonary segmental lavage with a dilute synthetic surfactant (Surfaxin) in 12 adults with ARDS. Patients received one of three dosing regimens in which aliquots of Surfaxin were administered via a wedged bronchoscope to each of the 19 bronchopulmonary segments. Suctioning was performed 10-30 s after instillation of individual aliquots. Group 1 patients (n ϭ 3) received one 30-ml aliquot of a 2.5-mg/ml concentration of Surfaxin in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 30 publications
0
58
0
3
Order By: Relevance
“…A significant number of clinical studies have reported benefits following the instillation of exogenous surfactants to term infants, children, or adults with ALI/ARDS or related acute respiratory failure [25,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] (Table 4). However, many of these are small case series or pilot studies, and found only improvements in acute lung function (oxygenation).…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of clinical studies have reported benefits following the instillation of exogenous surfactants to term infants, children, or adults with ALI/ARDS or related acute respiratory failure [25,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135] (Table 4). However, many of these are small case series or pilot studies, and found only improvements in acute lung function (oxygenation).…”
Section: Current Studies On Surfactant Replacement Therapy In Patmentioning
confidence: 99%
“…Two important conceptual approaches being followed to develop synthetic exogenous surfactants are: (1) Combining human sequence recombinant proteins or synthetic amphipathic peptides with synthetic biological glycerophospholipids; and (2) combining synthetic amphipathic peptides with novel synthetic lipids designed to have favorable physicochemical properties such as high surface activity and structural resistance to inflammatory phospholipases during lung injury. Surfaxin® (KL4) [87,107,123,[189][190][191][192][193][194][195] and Venticute® (recombinant SPC surfactant) [26,[196][197][198][199][200][201] are two current examples of the first of these approaches (Table 3). However, the 21 amino acid KL4 peptide is only a very rough structural analog to native SP-B, and advances in peptide molecular modeling and synthesis technology support the feasibility of preparing new SP-B peptides with significantly greater sequence and molecular folding specificity, and correspondingly higher activity ( [202][203][204] for review).…”
Section: Examples Of Research On New Synthetic Exogenous Surfactamentioning
confidence: 99%
“…(29) These animal studies on exogenous surfactant lavages are very impressive but in the literature there are no trials in humans except for a few small studies done in adults and in older children using the bronchoscope. (31)(32)(33) The bronchoscope allows reduction of the total volume of lavages to 1-3 cc/kg, decreasing side effects from larger volumes but it requires a lot of expertise in the management of such respiratory unstable patients during this invasive procedure. Nevertheless, in treated subjects most of the studies showed an improvement in gas exchanges.…”
Section: Paediatric Studiesmentioning
confidence: 99%
“…Сна чала препарат вводят в малой концентрации 2,5 мг/мл, а затем в том же объеме (по 30 мл в каждый сегмент) с концентраци ей 10 мг/мл. Суммарная доза препарата в сутки составляет 120 мг/кг [150]. Необходимо еще раз подчеркнуть, что тера певтические дозы разных препаратов отличаются и потому, что состав препаратов также различен.…”
Section: терапевтическая эффективность препаратов лсunclassified